Desconhecida pela comunidade e desprezada pelas autoridades: a biblioteca pública no Brasil na opinião de atores políticos e pesquisadores - (:unkn) unknown (Universidade Federal do Rio de Janeiro / Insitituto Brasileiro de Informação em Ciência e Tecnologia, 2015)
The thesis was focused on the situation of Brazilian public libraries, from the perspective of political actors and researchers who, in some way, were or are still connected to these institutions. In interviews performed from June 2014 to February 2015, questions were raised about the possible institutional crisis today, the impact of information and communication technologies (ICTs), the situation of Brazilian libraries and their relationship with the community, as well as expectations on a specific plan for the area. To support the empirical survey, it toured briefly the literature addressing the institution's history, showing how it has always been adapted to its context, and the view of its relationship with its audience, its community, has also changed. The literature pointed to issues that contribute to a new understanding of the institution in the use of ICTs in the formation of citizenship and relations with the community, to that effect appearing highlighted the idea of public library, as creator of social capital. Regarding the Brazilian libraries, the thought and action of three outstanding intellectuals who reflected and acted in the public library area were considered. The development of policies for the area was also analyzed, and illustrated with good practice in public libraries. The methodology adopted was semi-structured interviews aiming to allow respondents freedom in formulating the answers. The opinions of respondents highlight the plight of Brazilian public libraries, and offer different angles to understand the institutional invisibility and its lack of prestige.
Keywords: Biblioteca pública. Cidadania. Comunidade. Capital social. Política de biblioteca pública. Public library. Citizenship. Community. Social capital. Public library policy.; Ciência da informação